Psychological Distress among Parents due to Their Children Having Cancer: A Systematic Review - Nurhidayah, Ikeu; Dewi, Ratih Kusuma; Hidayati, Nur Oktavia; Poddar, Sandeep (UI Scholars Hub, 2022)
As a result of their children's cancer, parents are at risk of experiencing psychological distress. Parental stress will affect their roles in providing emotional support for their children. This systematic review aimed to identify the psychological distress of parents having children with cancer. EBSCO, PubMed, Science Direct, and Research Gate were applied to conduct electronic searches. The terms